An Utilization of Used Cooking Oil and Cassava Peel as Degradable Bioplastic Film - Mat Zin Boestami, Rusyidah Binti (Journal of Sustainable Natural Resources, 2020)
Abstract: Plastic product has become a main thing that used in human daily life. Mostly after the plastic are used, it will be a waste. Only small percentage of plastics are recycled and the rest will end up at landfills, rivers and oceans. Normally, plastics can take up to 1000 years to decompose in landfills and some will be burnt. The affect from burning the plastic waste in landfills will cause air pollution. When it burns with food waste, they will produce dioxin and furan. These elements will cause death even in small quantities when human breathe. Another harmful effect of burning plastic waste, is it can damage the ozone layer. Moreover, plastic pollution can affects all living things. At least 100 million marine mammals have died each year because of these plastic pollutions. The main objective of this research is to conduct starch extraction from cassava peels and glycerol extraction from waste cooking oil. It has been achieve during the extraction of 100g cassava peel will yield 3% of starch, while 800ml waste cooking oil yield of 5% only. The best formulation of the bioplastic obtained by controlling the ratio of carrageenan and starch at 2% and 5%. From the physical properties studies which is degradation in water and steam test. Based on the observation of degradation test, when the temperature was at 100ºc the bioplastic degrade within 1.18 minutes and at 20ºc was within 7.33 minutes. For the steam test, only at 100ºc the bioplastic start to degrade within 25minutes but for other temperature the plastic remains same. As a conclusion cassava starch can be utilized as bioplastic film, because it can dissolve when contact with water and steam. Moreover, glycerine from waste cooking oil can be used as plasticizer.